2012
DOI: 10.1631/jzus.b1200120
|View full text |Cite
|
Sign up to set email alerts
|

Topical imiquimod treatment of cutaneous vascular disorders in pediatric patients: clinical evaluation on the efficacy and safety

Abstract: Abstract:Objective: To evaluate the clinical effect of topical imiquimod treatment on cutaneous vascular disorders in pediatric patients. Methods: A retrospective investigation was conducted in 25 pediatric patients with cutaneous vascular disorders, including 19 infantile hemangiomas (IHs) (12 superficial/7 mixed type), 5 nevus flammeus (NF), and 1 pyogenic granuloma (PG). Imiquimod 5% cream was applied every other day for 4 to 16 weeks (average 9.6 weeks). Results: Of the 19 IHs treated, an overall efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…In the reports related to the CQ: Drug type: The drugs were classified into imiquimod, timolol, propranolol, corticosteroid, and others Drug concentration and dosage form: Imiquimod was used as a 5% cream, timolol as 0.5% ophthalmic solution or gel, propranolol as 1% ointment, and corticosteroid were often used as ointments of agents ranked as relatively strong such as clobetasol propionate, halobetasol propionate, and betamethasone dipropionate Methods for topical application: Frequent administration methods were once a day every other day for imiquimod, 2 times a day every day at 1–2 drops each time for timolol, 2 times a day every day for propranolol, and 2 times a day every day for corticosteroid. Methods for efficacy evaluation: Comparison of gross findings and photographs were adopted in all papers.…”
Section: Resultsmentioning
confidence: 99%
“…In the reports related to the CQ: Drug type: The drugs were classified into imiquimod, timolol, propranolol, corticosteroid, and others Drug concentration and dosage form: Imiquimod was used as a 5% cream, timolol as 0.5% ophthalmic solution or gel, propranolol as 1% ointment, and corticosteroid were often used as ointments of agents ranked as relatively strong such as clobetasol propionate, halobetasol propionate, and betamethasone dipropionate Methods for topical application: Frequent administration methods were once a day every other day for imiquimod, 2 times a day every day at 1–2 drops each time for timolol, 2 times a day every day for propranolol, and 2 times a day every day for corticosteroid. Methods for efficacy evaluation: Comparison of gross findings and photographs were adopted in all papers.…”
Section: Resultsmentioning
confidence: 99%
“…Anecdotal case reports also showed resolution of several other vascular tumors such as pyogenic granuloma, epithelioid hemangioendothelioma, angiolymphoid hyperplasia with eosinophilia, and lymphangioma circumscriptum with imiquimod treatment.…”
Section: Off‐label Uses Of Imiquimod In Cutaneous Disordersmentioning
confidence: 92%
“…Since an initial report showing imiquimod's potential in accelerating infantile hemangioma (IH) regression, more evidence have emerged on the efficacy of imiquimod in the treatment of several cutaneous vascular tumors or disorders including Kaposi's sarcoma (KS), pyogenic granuloma, among others . Imiquimod‐induced regression of vascular tumors is probably mediated by its immunomodulatory and anti‐angiogenic effects…”
Section: Off‐label Uses Of Imiquimod In Cutaneous Disordersmentioning
confidence: 99%
“…The antitumorigenic effect of corticosteroids is mediated by vasoconstriction, hormonal influences, and inhibition of angiogenesis . Recently, it was reported that topical imiquimod treatment affects human infantile hemangioma, including ulcerated ones and mouse hemangioendothelioma . Some reports suggested that imiquimod inhibits the growth of hemangioendothelioma through induction of TIMP1 expression, which is a known inhibitor of angiogenesis and cell motility …”
Section: Discussionmentioning
confidence: 99%
“…Pulsed dye laser, local corticosteroid injection, or external application of imiquimod cream has been administered in the management of some vascular tumors, including hemangiomas of infancy. [27][28][29][30] The pulsed dye laser produces an antitumorigenic effect by inducing destruction of the vascular wall, which results from the generation of thermal energy as the laser light is absorbed into hemoglobin within the lumina. The antitumorigenic effect of corticosteroids is mediated by vasoconstriction, hormonal influences, and inhibition of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%